Ingenious Fashion Marketing Comprehending Technology - Garg, Abhinav; Rajaram, NJ (International Journal of Computer Sciences and Engineering, 2025)
A decade back television, radio, newspaper, magazines, and billboards were among the major channels that placed advertisements, but now the trend has changed. A completely new era of marketing has opened up. The advancement of the mobiles, smart phones, Internet and the World Wide Web (WWW) has incredibly changed the lives of people. Using the Internet and the WWW, users are able to express their information requests, navigate specific websites and perform e-commerce transactions. This paper explores innovative marketing strategies which fashion companies are employing to outshine in today’s cut-throat market competition.